Language Materiality and Transmodal Production in EFL Classroom: The Case of Dayaknese Students - Handayani, Magpika; Luciana, Luciana; Sugiharto, Setiono (Jurnal Arbitrer, 2025)
Globalization has ushered English language teaching (ELT) to a radical shift which results in the incorporation of post-humanist paradigm in ELT. Ironically, however, this paradigm has not been thoroughly considered in ELT in periphery contexts where sociocultural-semiotic symbols as language materiality abound. In this article we consider language materiality as part of cultural materiality and social life which highlights transmodal elements a key concept in parallel localization within communities. The present study examines how the indigenous Dayak community in Kalimantan, Indonesia, utilizes materiality and transmodal production in EFL classrooms to facilitate knowledge construction through interactions with diverse objects, symbols, and resources. An instant ethnography was employed to capture transmodal moments, such as from writing to speaking, video to text, or speech to action, which result in dynamic transformations and expansions of meaning in the multimodal discourses classroom to students who have not previously learned English in their primary school. Multimodal Conversation Analysis (MCA) was used to analyze the data, which revealed that materiality is a transmodal production that encourages students to create meaning via their own lenses. As the students immersed themselves in the phase-by-phase engagement with semiotic symbols related to their English classes, the result shows that they improved their communication skills, comprehension, and access to knowledge. Based on their understanding of English, the knowledge they gain provides them with the opportunities to think critically. Furthermore, transmodal through materials can be applied as sources for students to make meaning.